The Effect of Import Tariff Reduction on Unemployment in Indonesia: Regional Level Analysis - Wulan Isfah Jamil; Arie Damayanti (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
The effect of import tariff reduction on unemployment can vary not only across sectors but also across regions, yet the empirical studies on regional analysis are still limited. This study investigates the effect of tariff reduction on unemployment in districts level in Indonesia spanning period 2000-2013. We follow the strategy of Topalova to construct regional tariff exposure in districts level. Our empirical analysis uses individual data approach to measure unemployment. By controlling the shifting in labor demand due to input tariff reduction, we find that import tariff reduction leads to an increase in unemployment and the increase is higher in district with larger employment share in net importer sectors.